A Chemometrics-Driven Strategy for Assessment of Treatment Efficacy: Contemporary Approach towards Effective and Individualized Treatments - Liljana Anastasova; Rumenka Petkovska (Current Progress in Medicine and Medical Research Vol. 5, 2023)
The aim of the study is to give a brief overview basic applications of several commonly used chemometric algorithms for multivariate data analysis in the field of assessment of treatment efficacy. Due to large amounts of measurement data proper data analysis is essential to understand the studied problem and obtain relevant information. The basic steps in the chemometric-driven strategy starting from data pre-processing, data modeling/exploration as well as modeling the differences among groups of data is presented together with some examples. Emphasis will be given on the basic characteristics and applications of the algorithms as well as some possible drawbacks of their use.